The Effect of Landscape Plants on the Human Psyche - Khurramovna, Sullieva Suluv; Sharofat, Xandalova (American Journal of Biodiversity, 2024)
Landscape plants play a significant role in enhancing human psychological well-being by reducing stress, improving mood, and promoting mental clarity. This study explores the psychological effects of exposure to landscape plants in various environments, including urban parks, suburban landscapes, and private gardens. Through a combination of literature review and field observations, the research identifies how landscape plants contribute to reduced stress levels, heightened positive emotions, improved attention, and overall mental well-being. Findings reveal that greenery and natural landscapes foster a restorative environment that enhances psychological health. These insights underscore the importance of integrating landscape plants into urban and residential spaces to support mental well-being in increasingly urbanized societies.